Analisis Psychological Well-Being Terhadap Keterampilan Berbicara Siswa Kelas IV SDN Samata Kecematan Somba Opu Kabupaten Gowa - Ris Adiwirasandi; Andi Adam; Sri Rahayu (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2023)
This research aims to investigate the influence of psychological well-being on students' speaking skills at elementary school level. The research method used was a survey involving a sample of students from SDN Samata. Data was collected through correlational research specifically designed to measure the influence of psychological well-being on students' speaking skills. The population in this study were fourth grade students at SDN Samata, Somba Opu District, Gowa Regency. The sampling technique used in this research was saturated sampling technique. The sample in this research was all 23 class IV students. The instruments used in this research were observation, speaking skills test, and psychological well-being questionnaire. Data analysis techniques were carried out using descriptive statistical techniques and inferential statistics. The research results show that there is a positive relationship between psychological well-being and students' speaking skills. Students' psychological well-being greatly influences students' learning achievements, especially speaking skills, such as the atmosphere in the classroom, students' play environment, students' family environment, students' mood, a pleasant atmosphere in the learning process, so that students can achieve better learning outcomes. These findings support the importance of psychological well-being in the learning process to increase learning effectiveness and efficiency. This research has important implications in the context of educational development. Educators can consider psychological well-being, in this case the psychological well-being of students, in determining strategies in the teaching process so that learning is more effective to improve student learning achievement, especially in speaking skills. In addition, educational institutions can pay more attention to students' psychological well-being to develop education. In conclusion, the results of this study highlight the positive impact of psychological well-being on student learning achievement, especially on speaking skills. Psychological well-being as one of the pillars of student learning achievement. Ultimately it can improve the quality of their academic results.